KECEMASAN KOMUNIKASI DALAM RELASI ANTAR ETNIS (STUDI PADA MAHASISWA ETNIS PAPUA DI UNIVERSITAS HALU OLEO) - Kasim Marewa, Asfiah Endang (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2016)
Abstract The purpose of this research is how type of anxiousness communication and what kind of element make something to come to the surface anxiousness communication of ethnic students of Papua on relation among ethnic in Halu Oleo University. This research aimed to identify and analyze: (1) anxiousnees communication form of ethnic students of Papua on relation among ethnic in Halu Oleo Universty, (2) what make something to come to the surface factor of anxiousness communication. The approach used in this research is anxiety/uncertainty management theory by William Gudykunst 1988, with qualitative research, this research apply purposive sampling as culling informant in a intentional manner grounded on aim and researcher’s requirement, with consideration that informant could hand over official statement concerning the problems that for perusal. The location of research carried on Halu Oleo University accompanying ten people from the students of Papua’s ethnic in Halu Oleo University. The data used in this research descriptive qualitative. The research findings showed that the form of anxiousness communication ethnic students of Papua on relation among ethnic on this research divide two shape: (1) indeterminancy on communicating the ethnic students of Papua exhibit hesitancy at the first time they braid connection with the others student, they disposed to cleared the track to do communicated to the others student whom they didn’t knew previously, as conciseness can we said that the indeterminancy turn up because the hesitancy. Interdeteminancy composed four matter one other thing: interdeteminancy at the early connection, alleviate process interdeteminancy, self identification, and self reliance the students of the ethnic students of Papua on relation among ethnic. (2) anxiousness communication be intended on this research is anxiety, hesitancy, afraid by perceived ethnic students of Papua on communicated. At this point divide on two shape: (a) surroundings situation, and (b) style of life some ethnic students of Papua cause something to be experienced disparity bringing on them to feel anxiousness when they initiate a communicating to the others student. Key word: Anxiousness Communication, Relation among ethnic, The Ethnic Students of Papua.